Masa lalu masalah lu: a semiotic study in the myths hidden within cigarette billboard ads in Indonesia - Abdul Manan; Muhammad Arif Fadhilah; Kamarullah; Luthfi Auni; Cut Intan Salasiyah (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Indonesian government has brought in strict regulations to stop cigarette advertisements, so cigarette companies have become very creative at creating subliminal messaging to promote their products. Our descriptive study discusses a semiotic analysis of billboard advertisements for brands of cigarettes in Indonesia. In particular, we focus on the signs’ function, how they deliver a message, and the implications or assurance for relieving daily societal problems. We also highlight the myths that these billboards deliver and their promises. Accordingly, 4 out of 52 large cigarette billboard ads on the streets around Banda Aceh, Indonesia, were selected based on specific considerations, namely brand popularity and frequency. The analysis of the ads draws on Chandler’s model of semiotic analysis covering the ads’ contextual background, description, interpretation, and explanation. The analysis shows that each ad uses various communicative functions to create a sense of motivation, pleasure, agitation, or conservatism. The ads also aim at rejecting Indonesians’ unawareness of problems, the boringness of routines, fantasy, and economic struggles. Each ad uses similar delivery ways in the colors, situation, and potential market target. As for the implication, the meanings represented by particular symbols in the ads are a way of life challenge and breaking boundaries despite the cigarette companies’ intention to persuade potential consumers to try their products.